2016
DOI: 10.1016/j.puhe.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of the inaugural International Summit for Medical Nutrition Education and Research

Abstract: Medical Nutrition Education (MNE) has been identified as an area with potential public health impact. Despite countries having distinctive education systems, barriers and facilitators to effective MNE are consistent across borders, demanding a common platform to initiate global programmes. A shared approach to supporting greater MNE is ideal to support countries to work together. In an effort to initiate this process, the Need for Nutrition Education/Innovation Programme group, in association with their strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…While international authors have been discussing the deficiency in nutritional education in medical schools and residency programs for over 30 years, proposing specific actions and conferences for this topic 37 , no studies were found that were carried out in Brazil among the researched literature using the descriptor formula. This is a matter of concern, since in Brazil, recent surveys have shown that more than 50% of the population is overweight and that the prevalence of hospital malnutrition can affect up to 60% of hospitalized patients 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…While international authors have been discussing the deficiency in nutritional education in medical schools and residency programs for over 30 years, proposing specific actions and conferences for this topic 37 , no studies were found that were carried out in Brazil among the researched literature using the descriptor formula. This is a matter of concern, since in Brazil, recent surveys have shown that more than 50% of the population is overweight and that the prevalence of hospital malnutrition can affect up to 60% of hospitalized patients 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…The work of NNEdPro focuses on developing adaptable and scalable models for nutrition education and combining clinical and public health knowledge with leadership training to aid and evaluate implementation in education, health care and community settings globally. The inaugural Summit in 2015 was an introduction to the dynamic interfaces between nutrition and health, with 2016 focused on setting priorities, and 2017 on implementing changes in policy and practice for sustained impact 7-9. The 2018 Summit authorised nutrition as a ‘hard science’ and inspired the need for high-quality data to inform nutrition policy and practice, as discussed in 2019 10 11.…”
Section: An Evaluation Of Global Knowledge Network In the Un Decade O...mentioning
confidence: 99%
“…The inaugural Summit in 2015 began as an introduction joining these interfaces, encouraging collaboration and setting the stage for next steps. 1 The 2016 event set global priorities leading to the 2017 event on how to implement changes for sustained impact. 2 3 2018 was dedicated to 'Nutrition as a Hard Science,' which inspired the focus on the need for the use of high-quality data in 2019.…”
Section: Introductionmentioning
confidence: 99%